Optimal integration of capacitor and PV in distribution network based on nomadic people optimizer - Hussein Abdel-Mawgoud; Salah Kamel; Sinan Q. Salih; Ali S. Alghamdi (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Since the last decades, capacitor and photovoltaics (PV) are installed in distribution networks to meet the increasing in system loads. In this paper, a new application of nomadic people optimizer (NPO) algorithm is proposed to obtain the best locations and sizes of capacitor and PV alone or simultaneously in radial distribution system (RDS). Also, reactive loss sensitivity factor (QLSF) can be used for obtaining the candidate locations for installing PV and capacitor units in RDS. The efficiency of the presented technique can be applied on IEEE 69-bus and IEEE 33-bus RDS. From simulation result, installing capacitor and PV units alone in RDS decreases the total losses and increases the bus voltages. Also, simultaneous integration of PV and capacitor units give better results than integration capacitor and PV units alone in distribution network. The presented algorithm is able to explore most area of search and obtain better results than recent optimizations algorithms.